Fakhr al-Din al-Razi on divine transcendence and anthropomorphism a refutation against the literalists - Mohd Farid Mohd Shahran (Islamic & Strategic Studies Institute, 2017)
As a religion which upholds divine transcendence as its fundamental element in arriving at divine knowledge, Islam is against any attempt to liken God with the characteristics of others particularly humans. The strong disavowal of anthropomorphism shown by Muslim theologians (the mutakallimūn) especially that against anthropomorphism brought by certain marginal schismatic sects throughout the history of Islamic thought has proved this uncompromising stance. This work analyses the refutations of one of the important later Ash'arite mutakallimun, Fakhr al-Din al-Razi (1149-1209) against the literal views of the anthropomorphism who invested God with various anthropomorphic qualities. Since anthropomorphism also springs from the false understanding of the ambiguous verses of the Qur'ān (mutashābihāt), this work examines al-Rāzī's views of muḥkamāt and mutashābihāt and the role of ta'wīl (allegorical interpretation) as the appropriate device in understanding the meaning of those ambiguous verses.